Genotyping of Croatian Olive Germplasm with Consensus SSR Markers - Snježana Bolarić; Aleš Vokurka; Kristina Batelja Lodeta; Đani Benčić (Horticulturae, 2024)
Leaf samples of 226 cultivated olive trees were collected from traditionally managed olive orchards and genotyped with eleven consensual SSR markers. The proportion of shared allele distance was used for the estimation of distances between olive genotypes. Cluster analyses were performed using a Fitch–Margoliash least-squares algorithm. The number of different genetic subgroups of olive genotypes (K) was investigated using STRUCTURE analysis. The standardization of allele lengths was performed to enable the comparison SSR profiles of Croatian olive genotypes with olive profiles obtained with the same SSR primers in OleaDB and WOGB databases. Overall, 73 SSR profiles of known Croatian varieties and 53 profiles of unknown olive genotypes were differentiated. Synonyms were detected in 18 varieties, and we found intra-varietal differences in 15 varieties. Three genetic subgroups of olive genotypes were determined. Following allele length standardization achieved using nine referral samples, the genetic profiles of 126 cultivated olive genotypes were compared to OleaDB and WOGB databases, out of which 92 genotypes were found to be unique to Croatian olive germplasm. The results revealed the wide genetic diversity of olive germplasm beyond the known, registered varieties. The FAZ_oliveDB database containing the profiles of 126 Croatian olive genotypes was created and made available for public use.